The Potential to Encode Detailed Information About Parasites in the Acoustic Signals of Chinese Horseshoe Bats (Rhinolophus sinicus) - Fan, Baozhu; Wang, Yujuan; Huang, Xiaobin; Zhang, Xianzheng; Yang, Jinting; Jiang, Tinglei (Frontiers in Ecology and Evolution, 2022)
Condition-dependent acoustic signals that potentially reveal information about the signaler’s physical or physiological condition are common and important in the animal kingdom. Given the negative effects of parasites on the health and fitness of their hosts, it is reasonable to expect animal acoustic signals to reflect detailed information concerning parasite infection. However, despite previous studies having verified the potential of sexually selected vocalizations to provide information on parasitism based on the correlations between call acoustic properties and parasitism in some animal taxa, less is known about whether acoustic signals used in a nonsexual context also reflect parasite infection especially for highly vocal bats. We thus investigated the relationships between the acoustic properties of distress calls and echolocation pulses and the infestation intensity of gamasid mites and bat flies in Chinese horseshoe bats (Rhinolophus sinicus) to determine whether acoustic signals potentially contain information about parasite infection. We found that bats infected with more gamasid mites uttered significantly shorter echolocation pulses, suggesting that echolocation pulses may contain information on the intensity of mite infection. Additionally, bats infected with more gamasid mites emitted distress calls with narrower bandwidth, while bats with more bat flies emitted calls with longer pause duration. These results suggest that distress calls may not only reflect a signaler’ parasite infection intensity but also may provide information concerning infection with specific parasites. In short, our findings suggest that acoustic signals of bats potentially reflect detailed information about parasite infection.